2005
DOI: 10.1002/cncr.21258
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of nasopharyngeal carcinoma in children and adolescents

Abstract: These participating institutions recruited patients into the study and are listed in alphabetical order. The number of patients recruited appears after each researcher's name. Departments of Pediatric Hematology and Oncology 1 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 63 publications
3
62
0
Order By: Relevance
“…The relatively short time to systemic failure in the absence of locoregional failure might suggest that subclinical metastasis that likely existed at first treatment required early systemic treatment. Two prospective multicentre studies, NPC-91-GPOH (Mertens et al 2005) and NPC-2003-GPOH/DCOG (Buehrlen et al 2012), demonstrated favourable results for multimodal treatment (neoadjuvant chemotherapy, and radiotherapy followed by interferon-β) in patients with paediatric and adolescent NPC. After a median follow-up time of 30 months and 48 months, the overall survival and event-free survival rates were 95–97% and 91–92.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively short time to systemic failure in the absence of locoregional failure might suggest that subclinical metastasis that likely existed at first treatment required early systemic treatment. Two prospective multicentre studies, NPC-91-GPOH (Mertens et al 2005) and NPC-2003-GPOH/DCOG (Buehrlen et al 2012), demonstrated favourable results for multimodal treatment (neoadjuvant chemotherapy, and radiotherapy followed by interferon-β) in patients with paediatric and adolescent NPC. After a median follow-up time of 30 months and 48 months, the overall survival and event-free survival rates were 95–97% and 91–92.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Young patients have more advanced disease at diagnosis and distant metastases are more frequently seen [4][9]. This might be caused by the undifferentiated state of the tumor, which is prone to develop distant metastasis [4], [6][7]. Another hypothesis is the late recognition of complaints belonging to NPC in young patients, since early symptoms of NPC are non-specific and can look like ordinary upper airway infections, which are common in children.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective trials have proven the benefit of additional chemotherapy in juveniles [4], [9][12]. Five-year disease-free survival varies between 45–77% and 5-year overall survival is 52–77% [5], [7][12]. Recently, Buehren et al published more promising results by adding adjuvant interferon beta after standard (chemo-) radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the five-year survival rate of NPC patients is between 10 and 40%3. Although many clinical trials have shown that patients receiving pre-radiation chemotherapy with methotrexate (MTX), cisplatin and 5-fluorouracil could significantly improve the five-year survival rate of metastatic NPC patients45, a considerable number of NPC patients develop drug-resistance and succumb to NPC as a result of disease progression. Therefore, new and effective treatments for NPC patients are urgently needed.…”
mentioning
confidence: 99%